Design of Metal‐Free Polymer Carbon Dots: A New Class of Room‐Temperature Phosphorescent Materials. Issue 9 (6th February 2018) - Tao, Songyuan; Lu, Siyu; Geng, Yijia; Zhu, Shoujun; Redfern, Simon A. T.; Song, Yubin; Feng, Tanglue; Xu, Weiqing; Yang, Bai
Abstract: Polymer carbon dots (PCDs) are proposed as a new class of room‐temperature phosphorescence (RTP) materials. The abundant energy levels in PCDs increase the probability of intersystem crossing (ISC) and their covalently crosslinked framework structures greatly suppress the nonradiative transitions. The efficient methods allow the manufacture of PCDs with unique RTP properties in air without additional metal complexation or complicated matrix composition. They thus provide a route towards the rational design of metal‐free RTP materials that may be synthesized easily. Furthermore, we find that RTP is associated with a crosslink‐enhanced emission (CEE) effect, which provides further routes to design improved PCDs with diverse RTP performance. Our results show the potential of PCDs as a universal route to achieve effective metal‐free RTP. Abstract : Room‐temperature phosphorescence : Polymer carbon dots (PCDs) showing metal‐free room‐temperature phosphorescence (RTP) have been constructed by using a facile method. The contribution of the cross‐link‐enhanced emission effect to the generation of RTP is verified and proposed as a guideline to forecast and synthesize a series of PCDs with diverse RTP performance (ISC=intersystem crossing).